Assessment of the Oral Health Care Practices and Basic Knowledge of Dental and Periodontal Diseases Among Dental Undergraduate Students: A Cross Sectional Study - Farhan Javed, Nazia Kalim, Ali Anwer, Shazma Iqbal, Saima Salman, Sana Chaudry, Sadia Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral health plays a vital role in overall health and quality of life. Hence, it is professional dutyof undergraduate dental students to possess good knowledge of a pristine oral health,all the pros of maintenance of it, cons pertaining to poor maintenance of it and thus be able to invoke awareness and impact the masses of a developing country like Pakistan, in a positive way. Aim: The aim of the study wasto assess thebehavior, attitude and knowledge of 2ndand 3rd year dental undergraduate students regarding practices and maintenance of good oral health. Methods:A Questionnaire was designed to assess the routine practices of the students, their habits and methods used for maintenance of good oral hygiene along with testing their basic knowledge regarding its influence over the oral and systemic health of the patient. Results: It was noted that the undergraduate students needed improvement in their practices of maintainingoral hygiene. Although in their clinical years, Third Year undergrads showed adequate knowledge but inferior oral hygiene maintenance practices as compared to their Second Year counterparts. Results obtained from the questionnaires distributed among the undergrads showed that 49.5% of 3DS, and 58.5% of 2DS used Modified Bass technique for brushing whereas usage of dental cleaning aids like wooden toothpicks, interdental brushes, dental floss and oral rinses was found to be 15.5%, 14.2%, 42.3% and 50.7% among 3DS whereas 20.5%, 25.4%, 50.8%, and 60.5% in 2 DS respectively. Variations in the basic knowledge of theundergrads regarding causative agents leading to tooth decay, diseases involving the periodontium and other diseases involving various systems of the human body, are shown in Table 3. Conclusion: The cross-sectional study we carried out among our dental students provided us with a new insight into knowledge, practices, condition and maintenance of oral health among dental students, the results of which, may help to reshape dental undergrad education and thus establish a model for dentists to improve oral health care awareness, practices and services. Keywords: Knowledge of good oral hygiene, Oral hygiene maintenance methods, Dental undergrad students, Pakistan.